Surgically correctable morbidity from male circumcision: Indications for specialist surgical care in Lagos - Adesoji O Ademuyiwa (Nigerian Journal of Surgery, 2012)
Aim/Objective: To determine the pattern of morbidity and outcome among patients referred to the Pediatric Surgery Unit of the Lagos University Teaching Hospital (LUTH) following circumcision. Materials and Methods: Retrospective descriptive study of all patients with complications of circumcision who were managed in LUTH between 2008 and 2010. Results: There were 36 patients. The age range was between 2 days and 9 years (median-3 months). Fifteen cases (42.9%) were due to urethro-cutaneous fistula while there were six cases (16.7%) of postcircumcision bleeding. There were four cases (11.1%) each of partial penile amputation and buried penis. There were also cases of meatal stenosis, penile implantation cyst and glanulo-preputial skin bridge. With respect to the treatment offered, eleven (30.6%) patients had urethroplasty for the urethro-cutaneous fistulae while seven (19.4%) patients had penile refashioning for the buried penis and penile amputation. Appropriate surgical treatments were performed for the other complications. Conclusion: Urethrocutaneous fistula and penile amputation are the commonest complications of circumcision for which referral is made to LUTH. Treatment outcome was satisfactory. Health education and legislation to ensure procedure is performed by qualified medical and paramedical staff may reduce the morbidity.